2004
DOI: 10.1016/j.molcel.2004.10.016
|View full text |Cite
|
Sign up to set email alerts
|

The RING Domain of Mdm2 Mediates Histone Ubiquitylation and Transcriptional Repression

Abstract: Histone modifications play a pivotal role in regulating transcription and other chromatin-associated processes. In yeast, histone H2B monoubiquitylation affects gene silencing. However, mammalian histone ubiquitylation remains poorly understood. We report that the Mdm2 oncoprotein, a RING domain E3 ubiquitin ligase known to ubiquitylate the p53 tumor suppressor protein, can interact directly with histones and promote in vitro monoubiquitylation of histones H2A and H2B. Moreover, Mdm2 induces H2B monoubiquityla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
191
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(196 citation statements)
references
References 49 publications
5
191
0
Order By: Relevance
“…Mdm2 is a ubiquitin ligase, which leads to p53 degradation, and also functions to repress p53 transcriptional activity. 38 It was found that the RING domain of Mdm2 mediates histone monoubiquitinylation and transcriptional repression. 38 By analogy with p53, it is tempting to speculate that besides the ubiquitination function of Itch, it might also mediate transcription repression, contributing to the regulation of gene silencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mdm2 is a ubiquitin ligase, which leads to p53 degradation, and also functions to repress p53 transcriptional activity. 38 It was found that the RING domain of Mdm2 mediates histone monoubiquitinylation and transcriptional repression. 38 By analogy with p53, it is tempting to speculate that besides the ubiquitination function of Itch, it might also mediate transcription repression, contributing to the regulation of gene silencing.…”
Section: Discussionmentioning
confidence: 99%
“…38 It was found that the RING domain of Mdm2 mediates histone monoubiquitinylation and transcriptional repression. 38 By analogy with p53, it is tempting to speculate that besides the ubiquitination function of Itch, it might also mediate transcription repression, contributing to the regulation of gene silencing. Therefore, by possessing the power to control both the transcriptional activity and the stability of transcription factors, transcription co-activators or repressors can quickly and efficiently influence transcriptional output and cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…34 Finally, Mdm2 induces monoubiquitination of histones surrounding the p53-response elements resulting in transcriptional repression. 35 Surprisingly, recent genetic studies fail to support a role for Mdm2 in the regulation of p53 transcriptional activity per se. Conditional inactivation of mdm2 leads to a dramatic increase in p53 levels accompanied by an increase in transcriptional activity.…”
Section: Mdm2 and Its Role In The Regulation Of P53 Transcriptional Amentioning
confidence: 99%
“…Recent studies on the functional significance of histone ubiquitination and the responsible enzymes have led to considerable advancement in our understanding (Minsky and Oren, 2004;Wang et al, 2004;Zhu et al, 2005). Unlike the most characterized function of protein ubiquitination, where four ubiquitin molecules are typically targeted to the protein, leading to degradation of the protein by the 26S proteasome, ubiquitination of histones often involves just one or two ubiquitin molecules covalently attached to the histones, resulting in mono-or diubiquitinated histone.…”
Section: Introductionmentioning
confidence: 99%
“…This modification does not lead to the ubiquitin-targeted degradation of histones (Osley, 2004). Recent studies have found a variety of functional consequences of this modification, including gene activation, repression, and DNA repair (Minsky and Oren, 2004;Wang et al, 2004;Cao et al, 2005;Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%